Physicochemical Properties, Antioxidant Activity and Organoleptic of Yogurt with The Addition of Red Dragon Fruit Juice (Hylocereus polyrhizus) - S. F. Siregar; A. Apriantini; M. S. Soenarno (Department of Animal Production and Technology, Faculty of Animal Science, IPB University in associated with Animal Scientist's Society of Indonesia (HILPI), 2023)
Yogurt is dairy product with high nutritional content, is obtained by fermentation process on fresh milk or milk solution with lactic acid bacteria. Yoghurt has a sour taste, to increase the sourness, natural flavourings from fruit juice are added. Red dragon fruit (Hylocereus polyrhizus) is one of thefruits that can be added to yogurt. Red dragon fruit (Hylocereus polyrhizus) is a fruit that contains antioxidants. The aim of this study was to determine the physicochemical characteristic, antioxidant activity and sensory properties of red dragon yogurt. The results showed that physical properties (pH,Aw, Viscosity and Total Titratable Acid) and chemical properties of ash content in red dragon yogurt has been accordance with SNI. The addition of red dragon fruit juice (Hylocereus polyrhizus) had significant affects (P<0.05) on the pH value, protein content, sensory properties of aroma, color, and taste. However, the addition of red dragon fruit juice (Hylocereus polyrhizus) did not give significant affect (P>0.05) to the Aw value, viscosity, total acid titration, ash content, color hedonic characteristics, texture, taste, texture hedonic quality characteristics. Yogurt with the concentration 10% of red dragon fruit juice had the best formulation compared to other concentration.